The Genetic Origin of Leucocytic Mucopolysaccharides in Cancer Patients - Riesco, A. (Nature Publishing Group, 1973)
The presence or absence of lymphocytic mucopolysaccharides (MPS) is studied in 223 subjects: 100 normals (controls); 8 cancer patients cured for more than 6 years; 30 cancer patients at the start of their treatment; and 85 relatives of first degree consanguinity of these last patients. The data are studied by statistical and genetic analysis. The results confirm the findings reported earlier and show that the difference in the probability of a high frequency of leucocytic MPS between the relatives of cancer patients and the controls is highly significant. Furthermore, this probability in a relative of first degree of consanguinity of a cancer patient is more than three times greater than in an individual of the general population. Genetic segregation analysis shows that the high leucocytic MPS trait segregates in the families of cancer patients after a classic pattern of dominant autosomal inheritance. Applying Falconer's nomogram it is concluded that the whole of this phenotypic variation is of genetic origin. Its interrelationships with cancer are discussed and it is postulated that this disturbance of the lymphocytic MPS represents a subclinical variant, not known until now, of the clinical mucopolysaccaridoses.